The Relationship of Stress to Blood Pressure and Body Mass Index in Pharmacy Study Program Students at Prima Medan University - Kristina Sirait; Meldawati Meldawati; Yeni Halim; Muhammad Aji Al-Faris (Green Publisher Indonesia, 2024)
Increased levels of academic stress in students can affect physical health, such as blood pressure and Body Mass Index (BMI). This study aims to determine the relationship between academic stress and blood pressure and BMI in Pharmacy Study Program students at Prima Indonesia University. This study used an analytical observational approach with a cross-sectional design, involving 4th semester students as research samples. Data were collected through the Perceived Stress Scale (PSS-10) questionnaire and measurement of blood pressure and BMI. Data were analyzed using Spearman's rho correlation test. The results showed a significant relationship between stress and blood pressure with a p-value of 0.029, but there was no significant relationship between stress and BMI with a p-value of 0.524. In conclusion, although there is a relationship between stress and blood pressure, stress levels are not directly related to BMI in university students. This study is expected to provide insight into the importance of stress management for student health.